Significance of arthrosonography for knee joint damage diagnosis in patients with early rheumatoid arthritis - L V Sizova; T V Chernyshova; G G Bagirova (Научно-практическая ревматология, 2008)
Objective. To assess significance of arthrosonography in diagnosis of in knee joint changes in patients with early rheumatoid arthritis (RA). Material and methods. 44 patients with early RA aged 19 to 73 years were examined. 29,5% of pts had early RA without primary osteoarthritis (OA), 70,5% had early RA with primary OA. Ultrasonography of knee joints was performed with Diasonics (USA, 1997) by the linear sensor with frequency of 7 MHz. The protocol of ultrasonic examination of knee joints was filled for each pt. Results. Clinical signs of of knee joint synovitis have been revealed in 61,5% of pts with early RA without primary OA, and in 80,6% of pts with early RA with primary OA, ultrasonic - in 100% of pts. Intraarticular knee joint effusion resulted in increase of suprapatellar bursa and lateral recesses size. Extraarticular inflammation was frequently shown by thickening of semymemranous muscles tendons, especially in pts with the early RA with primary OA (p<0,005). Degenerative changes in the group of pts with primary OA were more expressed in early RA and usually accompanied by non-uniform decrease of cartilage thickness and occurrence of osteophytes while cartilage in pts with early RA without primary OA had normal thickness or thickening because of swelling, and osteophytes were absent. Conclusion. Prevalence of knee joint intraarticular and extraarticular inflammatory changes over degenerate changes (symmetric thickening of the synovium, primary increase of the sizes of suprapatellar bursa and lateral recesses because of effusion, thickening of tendons of knee joints at the normal or increased thickness of cartilage because of inflammation) can be considered sonographic sign of early RA. In pts with early RA coincided with primary OA these changes were usually found in combination with non-uniform decrease of cartilage thickness. In case of cartilage inflammatory edema, detection of osteophytes allows to confirm presence of OA in pts with early RA.